Between sexual education and lust in patricia cabot's educating caroline (2001): a psychoanalytic perspective - Sari, Efayanti Puspita, Dr. M. Thoyibi, M.S, Titis Setyabudi, S.S. M. Hum (2014)
The major issue of this study is how the conflicting values between Sex Education and lust reflected in Patricia Cabot's Educating Caroline (2001): A Psychoanalytic Prespective. The objective of this study is to analyze the novel based on its structural elements and to analyze the novel based on psychoanalytic perspective. The research is qualitative study. The researcher uses primary data and secondary data. Primary data are taken from the prologue, dialogues, character's description, plot and all of the statement related to the problems and the secondary data sources are collected from other sources related to the research like the dictionary, website, and also the book related to the research in Psychoanalytic. The data collection method is library research by reads the novel, taking notes of the important parts and browsing to the internet to get some information. The data analysis method is descriptive qualitative analysis based on psychoanalytic perspective. The results of the study shows: firstly, based on the structural analysis, it can be concluded that in this novel the author conveys a moral messages that "The long term relationship can change People's view, wants and needs, especially in love". Secondly, based on psychological analysis it can be concluded that in the novel the author illustrates a psychological phenomenon in which behavior may change in the course of time bacuse of the intense relationship. The intense relationship can change the feeling and also emotion.